Pelatihan Pengembangan Usaha Melalui Pembaruan Desain Label Kemasan Pada UMKM Kacang Telur di Lappacinrana Kabupaten Sinjai - Yunita, A Reski; Nazaruddin, Nazaruddin (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are community economic activities that stand alone, are small scale, and are managed by community groups or families. The product label is the identity of a product that will be marketed. Product labels can make it easier for consumers to choose the product they want to buy and become a business brand booster in an increasingly competitive industry. Therefore, labels are very important so that these products can be recognized by the general public. Lack of interest and a market reach that is not too broad make this business not very well known among the general public. This is influenced by elements of product sales such as service quality, product, marketing, and packaging, which also support each other. After going through several innovations, it is certain that sales will increase and consumer interest in these pastries will increase. Existing social media can also be used to make sales. The business activities that are owned have developed. This is evidenced by the response of business actors who say that the marketing sector for their products is starting to expand and that their products are starting to be recognized by their buyers due to the display of labels on the packaging of their business products.